Proton Exchange Membrane Fuel Cell Model Validation Using Equivalent Electrical Circuit - Abdul Mubin, Ayu Nurfatika (2018)
Fuel cell is one of the most preferable renewable energy power sources nowadays due to its simplicity,capability, high efficiency,quick start-up,is environmentally friendly and has no geographical limitations.PEMFC is effective in the transformation of input energy into electrical energy and has been seen as being a great potential power source for the future.Because of its potential,there have been many experiments and empirical studies which have been carried out in both the academic and industrial fields.The focus of most research has been on the steady-state analysis of PEMFC.It is important to consider PEMFC reactions within this research as well.The processes of the PEMFC were implemented by modelling mathematical and electrical models using Matlab/Simulink simulation software.Both of the models were developed as two types of models which were steady-state and dynamic model to provide a comparison of the consideration of charge-double layer capacitance (CDL) and thermodynamic effect.Apart from that,to develop a more accurate model, both of the models were modelled by following the realstack specification of the 500-W PEMFC system which was manufactured by Horizon Pte.Ltd.Both models showed a different output response and the parameter of the losses was dependent on the duration of the simulation, temperature and the hydrogen pressure.The output of both models which differed in the stack output voltage,rated power,efficiency and time response of the model,were discussed.The parameters used were verified by testing the model with different values of reference temperature and the input hydrogen pressure.From that,the PEMFC emulator was also designed and built to verify the use of the parameter values in the modelling.The output obtained was analysed and discussed.The model produced an output with an efficiency higher than 30% compared with the H- 500 PEMFC specification efficiency of 40% which makes the model eligible for further development purposes.The parameters of reference temperature and input hydrogen pressure were suitable for the model and were verified.